Pseudo Papillary Tumor of Pancreas in a Child - Baloch, Farhan Abbas (International Journal of Pathology, 2018)
Abstract Solid pseudopapillary tumor of the pancreas is a rare pancreatic tumor. Mostly these tumors are found inwomen who are in their third decade of life. The tumors have a low malignant potential. A case of 9-year-oldfemale was observed who presented with dull abdominal pain, abdominal heaviness, mass abdomen for 2 and ahalf years duration. The mass was excised. The histopathological examination revealed Pseudo Papillary Tumorof Pancreas.